E-learning Service Framework Implementation for COVID-19 pandemic (Case study Informatic dept. Universitas Muhammadiyah Magelang) - Purwono Hendradi; Mohd Khanapi Abd Ghani; Siti Nurul Mahfuzah Mohamad; Dimas Sasongko (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Work from home is a way to reduce the development of the coronavirus termed COVID-19. In the world of education, we have been familiar with e-learning systems where learning is done with any time, any ware, anybody, and anyplace. Nevertheless, the readiness for implementation is not relaxed because there are technical and non-technical obstacles. There are four roles in e-learning wherein the role of instructor and student's role is the core, but the readiness of infrastructure and integration between systems is a problem in itself. The consequence of Work from home is to provide resources independently at home, with cost and geographical challenges. The development of E-learning 3.0, with its U-learning concept, gives a different dimension, especially in the use of cloud service provider applications. In this paper, the E-learning Service Framework is proposed by considering the results of a review of the LearningCube modeling, Interactive Mode Architecture, and Critical Success Factors.